The deep-sea fish digenean genus Tellervotrema Gibson & Bray, 1982 (Opecoelidae: Plagioporinae): Re-evaluation of the type species, T. armstrongi Gibson & Bray, 1982 and T. beringi (Mamaev, 1965) - Blend, Charles K.; Dronen, Norman O.; Gardner, Scott L.; Racz, Gabor R.; Armstrong, Howard W. (Zootaxa, 2012)
Tellervotrema Gibson & Bray, 1982 (Digenea: Opecoelidae) was erected for Podocotyle-like species that possess asymmetrical pair of isolated groups of vitelline follicles in the posterior forebody, lack them dorsal to the caeca andparasitize archybenthal macrourid fishes. Tellervotrema armstrongi Gibson & Bray, 1982 is redescribed from the typehost, the common Atlantic grenadier, Nezumia aequalis (Günther), N. cyrano Marshall & Iwamoto, and from anunidentified macrourid collected from the northern Gulf of Mexico. Tellervotrema beringi (Mamaev, 1965) is redescribedfrom the giant grenadier, Albatrossia pectoralis (Gilbert), and Coryphaenoides sp. obtained from off Oregon. Thefollowing six features are suggested to distinguish T. armstrongi and T. beringi: egg size; position of the genital pore;posterior extent of the cirrus-sac relative to the ventral sucker; testes volume relative to hindbody size; anterior extent ofthe paired vitelline groups in the forebody; and geographic locality. The generic diagnosis of Tellervotrema is amended toinclude circumcaecal vitelline follicles, and the presence of the vitelline gap itself was found to be a more consistentdiagnostic generic character than the location of the resulting pair of distinct, isolated groups of vitelline follicles createdby the gap. A neotype and paraneotypes are designated for T. beringi. The following new host and locality records areestablished: first original report of T. armstrongi from N. cyrano; first report of a member of Tellervotrema from the giantgrenadier, A. pectoralis; and the waters off Oregon are a new locality record for Tellervotrema, a genus in the North PacificOcean known only from the Bering Sea and off Japan. A comprehensive listing of all parasites previously reported fromthe four macrourid species examined herein is given and intermediate hosts are postulated through which species of Tellervotrema may complete their life cycles in the deep.